On the identity of Cheiracanthium orientale Kulczynski, 1885 (Aranei: Cheiracanthiidae) from Kamchatka, northeastern Siberia - Marusik Yuri M. (KMK SCIENTIFIC PRESS LTD, MOSCOW STATE UNIV, 2025)
Here I report the result of examining the syntypes of Cheiracanthium orientale Kulczynski, 1885, which was described from Kamchatka and later synonymized with C. erraticum (Walckenaer, 1802). This synonymy, which has been overlooked in several catalogs, is confirmed here. Distribution records of Ch. erraticum in northeastern Siberia are mapped.